Intake port flow study on various cylinder head using flowbench - Mohd Taufiq, Abd Kadir (2008)
Modification on intake port flow by enlarging the intake port area can increase engine performance. Higher air flow rate entered the intake port resulting higher air-fuel rate burn thus increased the performance of the engine. This report are consist of experiment of intake port flow between two cylinder head, Toyota 4AGE 1.6L and Proton 4G92 1.6L.Modification works will be porting, polishing, removing both cylinder head are experimentally tested by opening valve lift with significant value by calculations using Superflow® SF-1020 Flowbench machine. The experiment will consist of intake valve flow rate, the effect of velocity stack and swirl motion in bore. It is proved by experiment result that porting, polishing and removal valve guide in the intake port area works significantly increased the flow into the engine and consequently changes the swirl speed to a higher values for both cylinder head and tremendous increased when the velocity stack is added along with the modification works.